2021
DOI: 10.1186/s12913-021-06647-2
|View full text |Cite
|
Sign up to set email alerts
|

How can dementia diagnosis and care for Aboriginal and Torres Strait Islander people be improved? Perspectives of healthcare providers providing care in Aboriginal community controlled health services

Abstract: Background Aboriginal and/or Torres Strait Islander people experience dementia at a rate three to five times higher than the general Australian population. Aboriginal Community Controlled Health Services (ACCHSs) have a critical role to play in recognising symptoms of cognitive impairment, facilitating timely diagnosis of dementia, and managing the impacts of dementia. Little is known about the barriers and enablers to Aboriginal people receiving a timely dementia diagnosis and appropriate care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 20 publications
(27 reference statements)
2
30
0
Order By: Relevance
“…These findings are in accordance to previous studies conducted across Australia, which have reported a lack of community awareness about dementia and the need for education programs to ensure carers of Aboriginal people living with dementia are well informed and to provide culturally appropriate care. 12,20 Our study also shows that there needs to be more awareness so that people do not feel shameful about it and deny that they are experiencing symptoms. There is a need for a more systematic approach to informing people about dementia in the community.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…These findings are in accordance to previous studies conducted across Australia, which have reported a lack of community awareness about dementia and the need for education programs to ensure carers of Aboriginal people living with dementia are well informed and to provide culturally appropriate care. 12,20 Our study also shows that there needs to be more awareness so that people do not feel shameful about it and deny that they are experiencing symptoms. There is a need for a more systematic approach to informing people about dementia in the community.…”
Section: Discussionmentioning
confidence: 64%
“…The findings from this study are in accordance with a similar qualitative study undertaken recently among ACCHO staff across Australia. 20 There was a general understanding by participants that dementia was related to 'losing your memory' and a 'change in behaviour'. Participants identified risk factors (alcohol, drug use, smoking and stress) and potential protective factors (good diet, exercise and social support).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations